Foreigners, Morals, and Audit: A Trilogy of Controlling Transfer Pricing Practices in Indonesia - Marota, Rochman; Supriyanto, Joko (PT Keberlanjutan Strategis Indonesia, 2026)
Transfer pricing practices remain a critical issue in international taxation, particularly for firms operating in emerging markets such as Indonesia. This study examines the influence of foreign ownership, tax morale, and audit quality on transfer pricing practices among companies listed on the Indonesia Stock Exchange (IDX). Grounded in agency theory, the study explores how conflicts of interest between management, shareholders, and tax authorities shape cross-border transfer pricing decisions. Using a quantitative approach with panel data regression analysis, the results show that all proposed hypotheses are supported. Foreign ownership has a positive effect on transfer pricing practices, indicating that multinational ownership structures facilitate profit shifting to lower-tax jurisdictions. Tax morale negatively affects transfer pricing behavior, suggesting that strong ethical values function as internal controls that limit aggressive tax avoidance. Audit quality also significantly constrains unfair transfer pricing practices, as high-quality auditors, particularly Big Four firms, serve as effective monitoring mechanisms that reduce information asymmetry. These findings highlight the importance of strengthening corporate governance and managerial integrity to enhance fiscal compliance. From a policy perspective, tax authorities are encouraged to intensify supervision of foreign-affiliated firms and promote greater transparency through enhanced sustainability and tax reporting.